CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) FOR ACHIEVING POSITIVE OUTCOMES OF STUDENTS COLLEGE - Sri Yuliani; Khulaifiyah Khulaifiyah; Andi Idayani (Universitas Negeri Padang, 2015)
This research was aimed to find out the positive outcome of students college of Content and Language Integrated Learning (CLIL) on skill subjects. The sample of this research u'as semester six students of Islamic University of Riau who were taking Microteaching and ESP subject. The total sample was 30 students by using random sampling technique. The design of the research was experiment research focused on Post equivalent research. The instruments were questionnaires, observation, and interview. The treatment was given for 8 meetings in form of the students' assignment in giving motivation (story, Al Quran verse, wise words) for about 5 to 7 minutes. Based on the result, the data showed that there was significant effect of CLIL on the students outcome. The effect of CLIL was the students were eager to hear other motivation activities for next meetings, moreover the students were familiar with these moral values which effected their life style and behavior. The conclusion was CLIL was a methodological approach particularly suitable for contexts where students leamt content through supplementary teaching materials to give positive outcome of students' college.